2016
DOI: 10.1039/c6ra15005e
|View full text |Cite
|
Sign up to set email alerts
|

Electronic properties of a pristine and NH3/NO2 adsorbed buckled arsenene monolayer

Abstract: The electronic charge density associated with the inter-frontier orbitals of (a) NH3 arsenene and (b) NO2-arsenene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…It was reported that NH 3 and NO 2 , which are weakly bound on bare arsenene, can readily be adsorbed to Ge-substituted arsenene. 226 hb-As doped with transition metals (Ti, V, Cr, Mn, Fe, and Ni) maintained the stability at room temperature and attained magnetization. While Sc and Cr doped arsenene retained its semiconducting character, Ti and V doped arsenene transformed to metal.…”
Section: Arsenenementioning
confidence: 92%
“…It was reported that NH 3 and NO 2 , which are weakly bound on bare arsenene, can readily be adsorbed to Ge-substituted arsenene. 226 hb-As doped with transition metals (Ti, V, Cr, Mn, Fe, and Ni) maintained the stability at room temperature and attained magnetization. While Sc and Cr doped arsenene retained its semiconducting character, Ti and V doped arsenene transformed to metal.…”
Section: Arsenenementioning
confidence: 92%
“…39,62 Similar to phosphorene, arsenene shows high sensitivity to nitrogenbased gas molecules. 173,334 Liu et al studied the adsorption of CO, CO 2 , N 2 , NH 3 , NO and NO 2 molecules on the buckled arsenene monolayer. 173 Among those gases, the NO x adsorbents have the largest charge transfer, indicating a potential greater change in conductivity.…”
Section: Gas Sensorsmentioning
confidence: 99%
“…The first-principles study, based on density functional theory (DFT), was calculated through the DMol 3 code. The generalized gradient approximation (GGA) with the Perdew-Burke-Ernzerhof (PBE) functional [18,19,22] was adopted in the simulation. However, GGA ignores the long-range electron effects, which led to the overestimation of van der Waals forces [24][25][26][27].…”
Section: Methodsmentioning
confidence: 99%
“…A 4 × 4 × 1 supercell containing 32 atoms was adopted with a vacuum space of 20 Å to guarantee there was no interaction between adjacent layers. An 8 × 8 × 1 and 16 × 16 × 1 k-points in the Brillouin zone were adopted to optimize the configurations and calculate the electronic properties, respectively [19,21]. The convergence tolerance for energy minimizations was 1.0 × 10 −6 Ha, for maximum force it was 0.002 Ha/Å and for geometry optimizations it was 0.005 Å, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation